Functional trajectories associated with acute illness and hospitalization in oldest old patients: Impact on mortality - Gallego-González, Eva; Mayordomo-Cava, Jennifer; Vidán, María T.; Valadés-Malagón, María I.; Serra-Rexach, José A.; Ortiz-Alonso, Javier (Frontiers in Physiology, 2022)
Background: The literature pays low attention to functional changes during acute illness in older patients. Our main objectives were to separately describe the different functional changes occurring before and after hospital admission in oldest old medical patients, to investigate their association with mortality, and identify predictors associated with in-hospital failure to recover function. Methods: Secondary analysis of data from a prospective cohort study conducted in a tertiary teaching hospital. The study followed the STROBE criteria. The sample included 604 consecutive patients aged 65 or older hospitalized for acute illness, discharged alive, and not fully dependent at baseline. Activities of daily living measured at baseline, admission, and discharge were used to classify patients into four functional trajectories depending on whether they decline or remain stable between baseline and admission (prehospital) and whether they decline, remain stable, or recover baseline function between admission and discharge (in-hospital). Multivariate models were used to test the association between functional trajectories with mortality, and predictors for in-hospital recovery. Results: Functional trajectories were: “stable-stable” (18%); “decline-recovery” (18%); “decline-no recovery” (53%); “in-hospital decline” (11%). Prehospital decline occurred in 75% and 64% were discharged with worse function than baseline. “In-hospital decline” and “decline-no recovery” trajectories were independently associated with higher 6- and 12-month mortality. Extent of prehospital decline and dementia were predictors of failure to in-hospital recovery. Conclusions: In acutely ill older people, differentiating between prehospital and in-hospital functional changes has prognostic implications. Lack of functional regain at discharge is associated with higher mortality at 6- and 12-months.